A Novel Radiological Classification System of the Proximal Humerus - Sangaletti, Rudy; Abuljadail, Salahulddin; Akkaya, Mustafa; Zanna, Luigi; Gehrke, Thorsten; Citak, Mustafa (Zeitschrift für Orthopädie und Unfallchirurgie, 2023)
Different anatomical variants have been reported for the proximal and distal femur. Given this context, the goal of our study was to answer the following question: Can we also identify different anatomical variants of the proximal humerus?Two hundred anteroposterior (AP) radiographs of the proximal humerus with an equal gender distribution and equal laterality per gender were reviewed. The metaphyseal diameter of the proximal humerus at the level of the anatomical neck (X) and the intramedullary diameter at 10 cm from the apex of the greater tuberosity (Y) were measured. A new ratio was established, based on both measurements (Y/X). Radiographs showed different anatomical variants: type A: Y/X < 0.3, type B: Y/X = 0.3–0.4, type C: Y/X > 0.4. Two observers reviewed the AP radiographs independently and blindly in 2 different sessions.Three different anatomical groups (A, B and C) were identified based on the 25th and 75th percentiles. A higher percentage of type C was observed among females and a higher percentage of type A among males. A high inter-observer reliability was noted, with a Cronbach’s alpha of 0.97 (ICC 0.96–0.98). The intra-observer reliability for observer 1 had a Cronbach’s alpha of 0.98.A novel radiological classification of the proximal humerus has been established based on 3 different anatomical types (A, B and C). Further studies are needed to establish whether the novel classification system can be used as an indicator for aseptic loosening of cemented or cementless total shoulder arthroplasty.
Keywords: proximal humerus; proximal humerus radiographs; proximal humerus classification; proximal humerus canal width; shoulder arthroplasty